Reflection on the conditions for the emergence of the banking and financial system in the context of economic reforms in Algeria - LAZREG , Mohammed (Journal of Research in Finance and Accounting, 2020)
Algeria has moved towards a market economy. In fact, the transition from a debt economy to a market economy where the capital market plays a major role in growth, in our view implies a comprehensive reform of the financing scheme of the national economy. The banking and financial system must make more efforts to improve quantitatively and qualitatively the financing of the economy in Algeria by strengthening prevention and supervision within the framework of good governance.